I have these definitions:

Let $A \subset E^N$ and $b \in E^N$. The translation of $A$ by $b$, denoted by $(A)_{b r}$ is defined as $$ (A)_b=\left\{c \in E^N \mid c=a+b \quad \text { for some } a \in A\right\} $$


The binary erosion of $A$ by $B$, denoted by $A \ominus_b B$, is defined as $$ A \ominus_b B=\left\{x \in E^N \mid x+b \in A \quad \text { for every } b \in B\right\} . $$ Equivalently, we may write $$ A \ominus_b B=\bigcap_{b \in B}(A)_{-b} . $$ and i have this example: \begin{aligned} & A A=\{(0,1),(1,1),(2,1),(2,2),(3,0)\} \\ & B=\{(0,0),(0,1)\} \\ & A \ominus_b B=\{(2,1)\} \end{aligned}

I am trying to make another example of the following \begin{aligned} & A =\{(0,2),(0,3),(1,2),(1,3),(2,2),(2,3),(3,0),(3,1 ),(3,2),(3,3),(3,4)\} \\ & B=\{(0,0),(1,0),(2,0)\} \\ & A \ominus_b B \end{aligned} but its not same than this video and i am desperate



You must log in to answer this question.

Browse other questions tagged .